MENGGAGAS DISEMINASI WARISAN KREATIF MELALUI PENGEMBANGAN EDUCATIONAL TOURISM (STUDI KASUS: ROMO YB MANGUN WIJAYA) - Fransisca Anita Herawati; FX Bambang Kusumo Prihandono (ENSAINS JOURNAL, 2020)
Abstract: The city of Yogyakarta has a "spirit" of hybrid culture, where creative actors are behind the dynamics of the city. Historically, Yogyakarta has legendary actors, who bequeathed their creativity to a new generation. The creative inheritance pattern works effectively by diffusing creative ideas through networking. The actor who occupies the position of the structural hole is the owner of high social capital and plays a very important role in the process of inheritance. Every network knit always flows information, ideas that collide with each other and create creativity and new spaces. The purpose of this study is to initiate the process of creative heritage dissemination through educational tourism activities. The research method used is descriptive qualitative by conducting document studies, interviews and observations in the process of data collecting. The case study strategy is used to explore the creative legacy of the figure of YB Mangunwijaya, a Catholic priest, who was also an architect, writer and also a figure who had a concern for the world of education. The dissemination process can be carried out with the use of documents / artifacts from the character, which are relived through tourism activities tailored to the era. Referring to the results of the study, tourism activities were chosen to maintain the continuity of the inheritance of creative ideas, which involved economic reinforcement for the actors. Tourism activities which are initiated lead to tourism activities that are based on principles: something to see, something to do, something to buy and something to share. Creative heritage exploration is done through visual, structure, ornament and curatorial. Targeted tourists are those who have concerns in the fields of architecture, literature, education, and the lower-class community empowerment movement.Keywords: dissemination; educational tourism; creative heritage Abstrak: Kota Yogyakarta memiliki “roh” budaya hybrid, di mana aktor-aktor kreatif berada di balik dinamika kota. Secara historis Yogyakarta, memiliki aktor-aktor legenda, yang mewariskan kreativitas kepada generasi baru. Pola pewarisan kreatif berjalan efektif dengan cara difusi gagasan kreatif melalui jejaring. Aktor yang menduduki posisi structural hole adalah pemilik modal sosial tinggi dan berperan sangat penting dalam proses pewarisan. Setiap rajutan jejaring senantiasa mengalirkan informasi, gagasan yang saling bertubrukan dan menciptakan kreativitas dan  ruang-ruang baru. Tujuan dari penelitian ini adalah menggagas proses diseminasi warisan kreatif melalui aktivitas pariwisata pendidikan. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan melakukan studi dokumen, wawancara dan observasi dalam proses pengumpulan data. Strategi studi kasus digunakan untuk mengulik warisan kreatif dari tokoh YB Mangunwijaya, seorang pastor Katolik, yang juga seorang arsitek, sastrawan dan juga tokoh yang memiliki konsern terhadap dunia pendidikan. Proses diseminasi dapat dilakukan dengan penggunaan dokumen/artefak karya dari sang tokoh, yang dihidupi melalui aktivitas wisata yang disesuaikan dengan jamannya. Mengacu pada hasil penelitian maka aktivitas pariwisata dipilih untuk menjaga keberlanjutan pewarisan gagasan kreatif, di mana  melibatkan penguatan secara ekonomi bagi para pelaku. Aktivitas pariwisata yang digagas mengarah pada aktivitas wisata yang berprinsip pada something to see, something to do, something to buy dan something to share. Eksplorasi warisan kreatif dilakukan secara visual, struktur, ornamen dan kuratorial. Target wisatawan yang diarah adalah orang-orang yang memiliki konsern pada bidang arsitektur, sastra, pendidikan, dan gerakan pemberdayaan masyarakat kelas bawah.Kata kunci: edukasi; pariwisata edukasi; warisan kreatif